Work Ethic, Self-Efficacy and Quality of Work Life Improving Quality of Nurse Communication in Inpatient Patient Care - Christever, Christever; Dewi, Sandra; Nofierni, Nofierni (Alta Dharma Publisher, 2025)
Background: The quality of nurse communication is a form of nurse performance which plays an important role in increasing visits and trust in hospital services, especially nursing services. The high quality of nurse communication reflects good and quality hospital services. Objective: The aim of this research is to analyze the influence of work ethic, self-efficacy and quality of work life on the quality of communication of inpatient nurses at Puri Cinere Hospital. Method: The research uses quantitative methods with the type of explanatory causality research with a cross-sectional study approach. One hundred samples were recruited in this study using the simple random sampling. The regression analysis was used to analyzed the data and examine the association between independent variables with the dependent variable. Result: The results of the research show that work ethic, self-efficacy and quality of work life together have a significant effect on the quality of communication of inpatient nurses at Puri Cinere Hospital. Empirically, work ethic has no significant effect on the quality of communication of inpatient nurses at Puri Cinere Hospital. Self-efficacy has a significant effect on the quality of communication of inpatient nurses at Puri Cinere Hospital. The quality of work life has a significant effect on the quality of communication of inpatient nurses at Puri Cinere Hospital. Recommendation: The health care services ned to consider the work ethic and self-efficacy to improve the quality of communication among nurses. The quality of work life also needs to consider in order to improve the quality of communication. Furthr study may develop some intervensions to improve the communication skill among nurses in order to improve the quality of health care service